Implementation Of Constructivism Learning Theory In Science - Dinelti Fitria; Jamaris; Sufyarma (CV. AFDIFAL MAJU BERKAH, 2021)
This study aims to identify and understand the implementation of constructivism learning theory in science. The method used in this study uses a library method or approach (library research). Data obtained through literature study. The results showed that constructivist teaching is based on the belief that learning occurs as learners are actively involved in a process of meaning and knowledge construction rather than passively receiving information. Teaching methods based on constructivist views are very useful to help students' learning. The following are practices derived from cognitive psychology that can help students understand, recall and apply essential information, concepts and skills. They are used to make lessons relevant, activate students' prior knowledge, help elaborate and organize information, and encourage questioning. Important concepts from this perspective are advanced organizers, analogies, and elaboration. Teaching science from a constructivist perspective aims to give students knowledge of science in such a way that they not only understand the concepts and principles of science, but also the significance of science learning